A case-control study on the association of hepatitis B virus infection and hepatocellular carcinoma in Northeast Brazil - Cotrim Helma; Mota Eduardo; Leite Livia; Silva Luciana; Lyra Luiz (Universidade de São Paulo, 1992)
Hepatitis B virus (HBV) serological markers were investigated in 40 incident cases of hepatocellular carcinoma (HCC) and in two age and sex matched control groups, comprising 40 patients with other cancers and 80 healthy individuals, resident in Bahia, Brazil. Serologic tests were done by radioimmunoassay. The study observed high proportion of seropositivity to HBsAg (42.5%) and of those presenting HBsAg or antiHBc (65.0%) among HCC cases, higher in men than women and in those aged 17 to 30 years old. HBsAg seropositivity among HCC patients was greater than in the control group with other cancers (7.5%) and in healthy controls (2.5%), corresponding to odds ratio estimates of 15.0 (95% CI 3.29, 68.30) and 33.0 (95% CI 9.13, 119.28), both statistically significant. HBeAg was not observed and antiHBe was present in 41.2% of cases, suggesting the absence of viral replication, possibly with viral DNA intergration into the hepatocyte genome. The presence of cirrhosis was associated with HBsAg seropositivity among HCC cases. A history of chronic alcoholism is shown to be more frequently related to those cases with cirrhosis. This study highlights the relevant association between HCC and HBV in Northeast Brazil, particularly for young individuals, and the high risk of development of HCC for HBsAg carriers.